Association between oral contraceptives and cervical cancer: A retrospective case-control study based on the National Health and Nutrition Examination Survey - Chong Guo; Bo Zhan; Meng-Yuan Li; Li Yue; Chao Zhang (Frontiers Media S.A., 2024)
Background: Cervical cancer is the fourth most common cancer among females globally, with a high incidence and high mortality among females in developing countries. This retrospective case-control study aimed to investigate the association between oral contraceptives and cervical cancer, on which insufficient evidence still exists.Material and Methods: To examine the association between oral contraceptives and cervical cancer based on 7,496 females aged over 20 years from the National Health and Nutrition Examination Survey, multivariable logistic regression conducted from 1999 to 2016 was used.Results: Contraceptive use was positively associated with cervical cancer risk. In model 1 (unadjusted), a 195% increased risk of cervical cancer was observed among those who used oral contraceptives (odds ratio [OR] = 2.27, 95% confidence interval [CI] = 1.39-3.98, p = 0.002) compared to those who did not. In addition, the ORs for the exposed population were 1.74 (95% CI = 1.05-3.08, p = 0.041) and 1.93 (95% CI = 1.16-3.44, p = 0.017) in model 2 (adjusted for age, race, and body mass index [BMI]) and model 3 (adjusted for education level, ratio of family income to poverty, drinking status, smoking status, number of pregnancies, age at first sex, number of sexual partners, and whether to receive the human papillomavirus (HPV) vaccine in addition to model 2), respectively. Furthermore, subgroup analyses stratified by age, smoking status, BMI, age at first sex, number of sexual partners, and whether to receive the HPV vaccine also revealed that oral contraceptives were significantly associated with cervical cancer.Conclusion: This study demonstrated that oral contraceptive use increased the risk of cervical cancer. In addition, the higher risk, including individuals older than 45 years, having a high BMI (≥30 kg/m2), being current smokers, and having more than five sexual partners, may contribute to the development of cervical cancer.